Humanized childbirth in Colombia: Prevalence and associated factors - Myriam Ruiz-Rodríguez; Arlin Martha Bibiana Pérez-Hernández; Flor de María Cáceres-Manrique; Cristina María Mejía-Merino; Elba María De La Cruz Bermúdez-Quintana; Darlynne Xiomara Alfaro-Benavides; Adrián Arcenio Hidalgo-Erazo; Fabio Alberto Camargo-Figuera (PLoS ONE, 2025)
In several parts of the world, women are subjected to disrespectful and offensive treatment during childbirth. Humanized obstetrics or humanized childbirth has emerged as a response to this situation, and it refers to a model of comprehensive care for labor and childbirth that focuses on the respect and dignity of the woman. This study was aimed at estimating the prevalence and factors associated with humanized childbirth, as perceived by women in six major cities in Colombia. An analytical, multicenter, representative cross-sectional study was conducted in a random sample of six Colombian cities, including the country’s capital. We included 1294 women who were over 14 years of age and who had an institution-assisted vaginal childbirth resulting in a live birth in 2018. The prevalence of humanized childbirth in the sample of participating cities was 32.9% (95% confidence interval, 30.4–35.5). The city of residence of the pregnant woman, the presence of health problems during pregnancy, attendance at an antenatal course, the sex of the attending professional, and the association between the involvement of an obstetrician–gynecologist and the occurrence of a humanized childbirth were examined. These results indicate the need to monitor compliance with existing regulations to ensure dignified, respectful, and humane care that prioritizes women.